Crowding in and crowding out in Pakistan: A Co-Integration Analysis of Public and Private Investment (1972-2015) - Mah Rukh; Malik, Fazle; Baloch, Dr Muhammad Asif (Journal of Business & Tourism, 2023)
Investments in both public and private are essential to Pakistan's economy. Public investment iscrucial for any nation's economic development, but private investment serves as a catalyst for the creation of jobs and income. The primary purpose of this stud y is to empirically examine the “crowding-out and crowding-in” effects of state spending on private investment in Pakistan. The 43 most recent years (1972–2015) of data were gathered and examined. The main data sources used for data collection were the “State Bank of Pakistan”, "the Economic Survey of Pakistan," and "World Development Indicators”. The researchers considered all forms of investment, including private investment, "government interest spending," “current government spending”, and current government spending transfer. In the analysis section, the “Augmented Dickey-Fuller” test was employed to gauge the stationarity of the variables. All of the study's variables were found to be non-stationary using the analytical tools. The results of the "vector error correction model" (VECM), which was employed to examine both long-run and short-run causation, illustrate that government interest spending has a substantial and encouraging impact on private investments.